La distribución de competencias entre el poder central y las autonomías territoriales, en los Modelos Federales Europeos (2007)
The article describes the systems of distribution of competences between the Federation and the Member States in Germany, Austria, Belgium and Switzerland. It emphasizes that two institution sensure the smooth running of the division of competences: the parliamentary Camera of territorial representation and the Constitutional Federal Court. The approach to these questions of the federalStates could contribute to the current debate on the restructuring of the territorial Colombian pattern,since any State, as Colombia, that seeks to deepen and advance in the path of the political decentralization must face up to the following tasks: the regulation of a clear delimitation of competitions,supplemented with appropriate cooperation mechanisms; the configuration of a territorial parliamentary Camera -which provides an effective way where the territorial intermediate entities can defend the irinterests when the laws of the Republic are elaborated and approved - and the existence of a judicial organ which resolves the territorial conflicts.